The stoichiometry and kinetics of biological heat generation in the aerobic stage of dual digestion - Messenger, John (Department of Civil Engineering, 2016)
Over the past 10 years the Water Research Commission (WRC) has recognized the potential benefits of the dual digestion system for South Africa where anaerobic digestion is the preferred method of sludge stabilization. Accordingly, from 1981 to 1984 under WRC sponsorship, the Johannesburg City Council (JCC) undertook a pilot plant study into the performance of the autothermal thermophilic aerobic reactor oxygenated with pure oxygen. As a consequence of the encouraging results obtained in this study (Trim and McGlashan, 1984; Trim, 1984), in 1987 the WRC and Milnerton Municipality supported a frill scale evaluation of dual digestion ( 45 ma pure oxygen oxygenated aerobic reactor and 600 ma anaerobic digestor) at Milnerton's Potsdam Wastewater Treatment Works, with scientific and academic input by the Division of Water Technology of the CSIR and the Department of Civil Engineering, of UCT. In this evaluation a number of important considerations needed to be addressed such as (1) oxygen requirements and oxygen utilization efficiency with pure oxygen and air oxygenation, (2) minimum retention time that can be achieved in the aerobic reactor and in the anaerobic digestor without comprormsmg the attainment of thermophilic temperature in the reactor and VS removal, gas production and sludge stability in the digestor, (3) temperature control of the aerobic reactor and anaerobic digestor, ( 4) efficacy of pathogen inactivation and mode of operation to prevent recontamination, (5) dewaterability of the anaerobically digested sludge, (6) operation and economic evaluation of the system. In this thesis, the results obtained pertaining to operation and performance of the Milnerton aerobic reactor are presented in detail. Also, the observed results are generalized and, based on the observed general principles, a design procedure and a simulation algorithm and computer programme for pure oxygen and air oxygenated reactors are developed, in accordance with objectives (1) to (3) above.